قضايا المرأة في فكر الشيخ مصطفى صبري - بالي, الزهرة; مسعي, زعيرة; عوينات, صفاء (جامعة الوادي university of eloued, 2017)
الم أ رة نصؼ المجتمع، ىذا كلب مبتذؿ لأنو يأتي بدكف تطبيؽ، فالم أ رة في كقتنا الحاضر عبارة عف سمعة كلكف لا ثمف ليا، فيي في ىذا الزمف تطالب بحقكقيا كتسعى إلى المساكاة مع الرجؿ كلكف لماذا تطالب بشيء ىك مكجكد أصلب في المطالبة تككف في الشيء المفقكد، فالإسلب أعطى لمم أ رة حقكقا ل تكف لتحصؿ عمييا مف سكاه مف الأدياف أك الش ا رئع أك القكانيف الكضعية، كمف الحقكؽ التي أعطاىا الإسلب لمم أ رة ىك حؽ الم أ رة في الحياة، ففي الجاىمية كانت منتشرة عادة كأد البنات. كفي د ا رستنا المتمثمة في د ا رسة كتاب شيخ الإسلب مصطفى صبرم الذم مكضكعو "قكلي في الم أ رة" الذم عرض فيو القضايا المثيرة لمجدؿ فيما يخص الم أ رة بالنصكص الشرعية مثؿ التعدد كالسفكر كالاحتجاب كالزكاج كغيره كفي مقارنة بحاؿ الغرب كحاؿ النساء في الحضا ا رت الإسلبمية فكؽ اختيارنا عمى كتاب قكلي في الم أ رة بالكقكؼ عمى أى القضايا التي عالجيا الشيخ مصطفى صبرم لرد عمى كؿ الشبيات التي تحؾ ضد حقكؽ الم أ رة في الإسلب. Reseach Summary Woman is half of our society but it only a general speak because it not applied in many regrons .Nowadays; Women Is like goods or merchandise but without a price. in this days she demand her rights end her equality with mam. although the exisence of her rights she pretend or demand them since EL Islam give her all rights which the ohich religions and the other lows don t have and talk about it for instance in ancient times thre are some bed traditions which spread and don t talk about her rights In our study of the study of Shaykh al-Islam Mustafa Sabri, entitled "Saying in Women," in which she presented the controversial issues in terms of women's legal texts such as pluralism, sorcery, marriage and other marriages. In contrast to the situation of the West and the status of women in Islamic civilizations, In women to stand on the most important issues addressed by Sheikh Mustafa Sabri to respond to all the suspensions that are woven against the rights of women in Islam
دعوة